The Dependence of Ancient Greek Geometry and Metaphysics on Craft-Culture - Thibodeau, Philip (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2020)
A discussion of Robert Hahn’s The Metaphysics of the Pythagorean Theorem: Thales, Pythagoras, Engineering, Diagrams, and the Construction of the Cosmos out of Right Triangles.